Phase 1, pharmacogenomic, dose‐expansion study of pegargiminase plus pemetrexed and cisplatin in patients with ASS1‐deficient non‐squamous non‐small cell lung cancer. (12th August 2021) - Szlosarek, Peter W.; Wimalasingham, Akhila G.; Phillips, Melissa M.; Hall, Peter E.; Chan, Pui Ying; Conibear, John; Lim, Louise; Rashid, Sukaina; Steele, Jeremy; Wells, Paula; Shiu, Chiung‐Fang; Kuo, Chih‐Ling; et al.
Abstract: Introduction: We evaluated the arginine‐depleting enzyme pegargiminase (ADI‐PEG20; ADI) with pemetrexed (Pem) and cisplatin (Cis) (ADIPemCis) in ASS1‐deficient non‐squamous non‐small cell lung cancer (NSCLC) via a phase 1 dose‐expansion trial with exploratory biomarker analysis. Methods: Sixty‐seven chemonaïve patients with advanced non‐squamous NSCLC were screened, enrolling 21 ASS1‐deficient subjects from March 2015 to July 2017 onto weekly pegargiminase (36 mg/m 2 ) with Pem (500 mg/m 2 ) and Cis (75 mg/m 2 ), every 3 weeks (four cycles maximum), with maintenance Pem or pegargiminase. Safety, pharmacodynamics, immunogenicity, and efficacy were determined; molecular biomarkers were annotated by next‐generation sequencing and PD‐L1 immunohistochemistry. Results: ADIPemCis was well‐tolerated. Plasma arginine and citrulline were differentially modulated; pegargiminase antibodies plateaued by week 10. The disease control rate was 85.7% ( n = 18/21; 95% CI 63.7%–97%), with a partial response rate of 47.6% ( n = 10/21; 95% CI 25.7%–70.2%). The median progression‐free and overall survivals were 4.2 (95% CI 2.9–4.8) and 7.2 (95% CI 5.1–18.4) months, respectively. Two PD‐L1‐expressing (≥1%) patients are alive following subsequent pembrolizumab immunotherapy (9.5%). Tumoral ASS1 deficiency enriched for p53 (64.7%) mutations, and numerically worse median overall survival as compared to ASS1‐proficient disease (10.2 months; n = 29). There was no apparent increase in KRAS mutations (35.3%) and PD‐L1 (<1%) expression (55.6%). Re‐expression of tumoral ASS1 was detected in one patient at progression ( n = 1/3). Conclusions: ADIPemCis was safe and highly active in patients with ASS1‐deficient non‐squamous NSCLC, however, survival was poor overall. ASS1 loss was co‐associated with p53 mutations. Therapies incorporating pegargiminase merit further evaluation in ASS1‐deficient and treatment‐refractory NSCLC. Abstract : We evaluated the arginine‐depleting enzyme pegargiminase (ADI‐PEG20; ADI) with pemetrexed (Pem) and cisplatin (Cis) (ADIPemCis) in ASS1‐deficient non‐squamous non‐small cell lung cancer (NSCLC) via a phase 1 dose‐expansion trial with exploratory biomarker analysis. ADIPemCis was safe and highly active in patients with ASS1‐deficient non‐squamous NSCLC, however, survival was poor overall. ASS1 loss was co‐associated with p53 mutations providing a developmental pathway for further testing pegargiminase in ASS1‐deficient and treatment‐refractory NSCLC.